Carotid Artery Angioplasty and Stenting for Carotid Stenosis: A Single-Center Experience from Saudi Arabia - Hussein Algahtani; Bader Shirah; Abdullah S. Alghamdi; Ahmad Subahi; Saeed A. Alqahtani; Abdulrahman Alshamy (Neurointervention, 2020)
Purpose Atherosclerotic stenosis of the extracranial carotid artery accounts for approximately 20% of all strokes. Both carotid artery endarterectomy and carotid artery angioplasty with stenting (CAAS) are recommended for symptomatic patients with 50% or more stenosis or asymptomatic patients with 70% or more stenosis. CAAS is under-reported in Saudi Arabia, as evidenced by a thorough literature search. In this article, we aim to share our experience of CAAS to call for the necessity of conducting more research on stroke and emphasize the local need of utilizing more endovascular treatments like CAAS. Materials and Methods A retrospective single-center observational study was conducted at King Abdulaziz Medical City in Jeddah, Saudi Arabia. The inclusion criteria consisted of all adult patients (18 years and above) with carotid stenosis who were treated with CAAS. Results A total of 16 patients were included in the study. The mean age of the participants was 66.9±13.5 years (range 30–87 years). All patients were symptomatic (had a previous stroke or transient ischemic attack). The procedure was successful in 14 patients (87.5%), while it failed in 2 patients (12.5%) due to technical reasons. All patients had no stroke or myocardial infarction within 30 days of the procedure. Conclusion Despite the advancement in medicine with free healthcare services in Saudi Arabia, the interventional procedures for secondary prevention of strokes are underutilized. Collaboration between different hospitals will be extremely helpful since few centers in each city are providing such treatments by an expert neurointerventionist and/or strokologist. The good selection of candidates, optimal management of comorbid conditions, and multidisciplinary care may improve outcomes and reduce mortality.